Area and Delay Efficient 2-D DWT using Canonic Signed Digit and Brent Kung Adder Technique - Choudhary, Anjulata; Pandey, Nishi; Shrivastava, Meha (International Journal of Computer Sciences and Engineering, 2019)
The DWT is expressed in a generalized form know as discrete wavelet transform which analyzes both the low and high sub bands with equal priority at every decomposition level. The DWT is a mathematical technique that provides a new method for signal processing. Due to various useful features like adaptive time-frequency window, lower aliasing distortion and efficient computational complexity, it is widely used in many signal and image processing applications. 2-D DWT is widely used in image and video compression. But flipping scheme introduces some design complexities in selected DWT structures. So in our proposed work, we have implemented BK adder and CSD technique that provides multiplier-less implementation and also will work for every bit. The proposed CSD and BK adder based 1-D and 2-D DWT algorithm shows good performance as compared to previous algorithm. The proposed architecture for DWT implementation reduces the chip area, less computation time and also minimizes the maximum combinational path delay.